Digital signal processing using Matlab - Ingle, Vinay K. (BookWare Companion series., 2000)
Discrete-time signals and systems; The discrete-time fourier analysis; The z-transform; The discrete fourier transform; Digital filter structures; Fir filter design; IIR filter design; Applications in adaptive filtering; Applications in communications.